Climate elements and their relationship with the Guatemalan Moth Tecia solanivora (Povolný, 1973) (Lepidoptera: Gelechiidae) in potato (Solanum tuberosum L.) crop - Wilches-Ortiz, Wilmar Alexander (2022)
Introduction. Climate variability and climate change scenarios influence the behavior of species and natural resources. The potato (Solanum tuberosum L., Solanaceae) crop produces a food of high nutritional value that is a staple in the family food basket. In Colombia, the production system is affected by pests, such as the Guatemalan potato moth caused by Tecia solanivora (Povolný), with few field studies describing its relationship with climate. Objective. To evaluate the effect of climatic elements on the adult male populations of T. solanivora in three potato crop cycles in a locality in Colombia. Materials and methods. In the municipality of Mosquera, Cundinamarca, Colombia, between November 2015 and October 2017, baited traps with sexual pheromone were located for the capture of adult Guatemalan potato moths in three potato cv Diacol capiro crop cycles, and the following were recorded: number of adults, precipitation (mm), relative humidity (%), minimum, mean, and maximum temperatures (°C), wind speed (km/h), solar brightness (h/day), agroclimatic indices of degree days (°Cd), reference evapotranspiration (mm/day), and water index (HI). Pearson and Dickey-Fuller tests, time series, and cross-correlation were performed. Results. The fluctuation of adults of T. solanivora was positively correlated with maximum temperature, degree days, and solar brightness, and a negatively correlated with precipitation (p<0.05). The maximum temperature (20 - 23 °C ±0.7 °C) presented the highest significance (p<0.05) of all the cross-correlations with Tecia solanivora, with a direct relationship when exceeding the autocorrelation coefficients, which increased the population and displacement of T. solanivora adults. The autocorrelation with precipitation (62 – 128 mm ±22 mm) showed population decrease (p<0.05). Conclusions. Climatic variables were critical limiting factors for the emergence and survival of T. solanivora.